Evaluating the preventive and curative effects of Toxocara canis larva in Freund's complete adjuvant‐induced arthritis. (15th June 2020) - Shayesteh, Zahra; Hosseini, Hamid; Nasiri, Vahid; Haddadi, Zeinab; Moradi, Najmeh; Beikzadeh, Leila; Sezavar, Monireh; Heidari, Aliehsan; Zibaei, Mohammad
Abstract: Helminthic infection and the parallel host immune reactions are the results of a protracted dynamic co‐interaction between the host and worms. An assessment of the effect of Toxocara canis infection on arthritis in rats stimulated by Freund's complete adjuvant (FCA) was the main purpose of the investigation. An arthritis model was established by the administration of 0.1 mL FCA in the palmar surface. Cytokine assessment, evaluating oedema and the use of a rheumatoid arthritis (RA) score provided evidence of the protective effects of T canis against adjuvant‐induced arthritis (AIA). The cytokines TGF‐β, IFN‐ɣ, IL‐10 and IL‐17 were measured to assess the anti‐inflammatory effect of T canis infection. Besides, arthritis swelling findings were evaluated in rat paws. The data showed that T canis infection significantly modulated the immune response by alleviating inflammatory cytokines and increasing TGF‐β as an anti‐inflammatory cytokine. Evaluations of arthritis swelling showed low severity and faster recuperation. These findings suggest that the products derived from T canis eggs might be a potential therapeutic candidate to treat autoimmune diseases like the arthritis.